Highly sensitive bending sensor based on multimode–multimode–coreoffset fiber structure. (December 2015) - Qi, Yanhui; Ma, Lin; Sun, Jiang; Kang, Zexin; Bai, Yunlong; Jian, Shuisheng
Abstract: In this paper, we present a simple fiber optic bending sensor based on the multimode–multimode structure combining with the core-offset fiber structure. The multimode–multimode structure is composed of no core fiber (NCF) with hundreds of micrometers in length as a micro-lens for mode conversion, and single mode fiber (SMF) which can be seen as a section of special multimode fiber (MMF) when considered the cladding modes. The transmission spectrum in the experiment agrees well with the numerical model. The sensitivity of the structure can be achieved as high as 11.104 nm/m −1 in the measuring range. Meanwhile, the sensitivity of the neighboring resonance wavelength around 1546 nm exhibits approximately the same sensitivity which is 10.579 nm/m −1 . Besides, the strain sensitivity is about −0.927 pm/με within the measuring strain range. Highlights: Both numerical and experimental investigation are presented. The experimental results follow the theoretical predictions. High sensitivity is achieved. Useful in the design, optimization and fabrication in optical fiber filter.